Efektivitas Audit Internal Pada Perusahaan Perkebunan di Sumatera Utara - Deliana, Deliana; Mahyuni, Sri (Jurnal Riset Akuntansi dan Keuangan, 2018)
Abstract. This study examained  effectiveness of  internal audit in plantation Companies North Sumatera.   The sample in this study were 43 people consisting of internal audit chief, team leader and internal auditor at plantation company in North Sumatera.  This study used descriptive analysis to analyze the responses of respondents on the questionnaire and hypothesis test using regression with SPSS software  The results of this study indicate that the support of top management and internal auditor competence affect the effectiveness of internal audit Keywords:. internal auditor competene ; internal audit effectiveness; Topmanagement support